Th17 CD4+ T-Cell as a Preferential Target for HIV Reservoirs - Renault, Constance; Veyrenche, Nicolas; Mennechet, Franck; Bedin, Anne-Sophie; Routy, Jean-Pierre; Van de Perre, Philippe; Reynes, Jacques; Tuaillon, Edouard (Frontiers in Immunology, 2022)
Among CD4+ T-cells, T helper 17 (Th17) cells play a sentinel role in the defense against bacterial/fungal pathogens at mucosal barriers. However, Th17 cells are also highly susceptible to HIV-1 infection and are rapidly depleted from gut mucosal sites, causing an imbalance of the Th17/Treg ratio and impairing cytokines production. Consequently, damage to the gut mucosal barrier leads to an enhanced microbial translocation and systemic inflammation, a hallmark of HIV-1 disease progression. Th17 cells’ expression of mucosal homing receptors (CCR6 and α4β7), as well as HIV receptors and co-receptors (CD4, α4β7, CCR5, and CXCR4), contributes to susceptibility to HIV infection. The up-regulation of numerous intracellular factors facilitating HIV production, alongside the downregulation of factors inhibiting HIV, help to explain the frequency of HIV DNA within Th17 cells. Th17 cells harbor long-lived viral reservoirs in people living with HIV (PLWH) who are receiving antiretroviral therapy (ART). Moreover, cell longevity and the proliferation of a fraction of Th17 CD4 T cells allow HIV reservoirs to be maintained in ART patients.